Strategic Management / An Integrated Approach: Fifth Edition - Hill W. Charles; Jones Gareth R (Houghton Mifflin Company, 1992)
Introduction to Strategic Management, The Strategic Management Series, Stakeholders and the Corporate Mission, The Nature of Competitive Advantage, External Analysis: The Identification of Industry Opportunities and Threats, Internal Analysis: Resources and Capabilities and Competencies and Competitive Advantage, Strategies, Building Competitive Advantage Through Functional Level Strategy, Business-Level Strategy, Competitive Strategy and the Industry Environment, Strategy in the Global Environment, Corporate Strategy: Vertical Integration and Diversification and Strategic Alliances, Implementary Strategy, Designing Organizational Structure, Designing Strategic Control Systems, Matching Structure and Control to Strategy, Implementing Strategic Change, Cases in Strategic Management.
Introduction to Strategic Management, The Strategic Management Series, Stakeholders and the Corporate Mission, The Nature of Competitive Advantage, External Analysis: The Identification of Industry Opportunities and Threats, Internal Analysis: Resources and Capabilities and Competencies and Competitive Advantage, Strategies, Building Competitive Advantage Through Functional Level Strategy, Business-Level Strategy, Competitive Strategy and the Industry Environment, Strategy in the Global Environment, Corporate Strategy: Vertical Integration and Diversification and Strategic Alliances, Implementary Strategy, Designing Organizational Structure, Designing Strategic Control Systems, Matching Structure and Control to Strategy, Implementing Strategic Change, Cases in Strategic Management.